Delayed rupture of the spleen in rheumatoid arthritis. - Taylor, J L (1990)
When tripping and falling patients with rheumatoid arthritis may adopt the 'fetal tuck' position to protect their painful deformed hands. There is then a risk of splenic injury by the left elbow, which may not be immediately apparent.